Beginner's Greek : a novel - Collins, James (New York : Little Brown and Company, 2008)
Peter Russell is a deeply romantic guy who believes the woman of his dreams is destined to sit next to him on an airplane. Holly is a pretty, strawberry blonde woman who reads Thomas Mann for pleasure. As Pete sits next to her, he falls deeply in love, and asks for her telephone number. Later that night in his hotel room, he discovers that the page from her book that contained her telephone number is gone.
Keywords: Married people -- Fiction; Adultery -- Fiction; Love stories